ANALISIS PENGARUH CORE SERVICE QUALITY DAN PERIPHERAL SERVICE QUALITY TERHADAP KEPUASAN PELANGGAN DALAM MENINGKATKAN MINAT MEREFERENSIKAN (Studi pada Rumah Sakit (RS) Islam Sultan Agung Semarang) - Murtadho, Muhamad (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2013)
he aim of this research is to investigate the influence of core service quality, and periphery service quality, toward customer satisfaction to increase word of mouth. Using these variables, the usage of these variables are able to solve the arising problem within customers in Sultan Agung Islamic Hospital.Population used in this research were 100 customers Sultan Agung Islamic Hospital. The analysis technique using Statistic Package Social Science (SPSS) software to analyze corelation betwen core service quality and peripheral service quality to customer satisfaction to increase word of mouth.The analysis results shows that influence of core service quality, and periphery service quality, have influence in customer satisfaction to increase word of mouth. The effect of core service quality on customer satisfaction are positive significant; The effect periphery service quality on customer satisfaction are positive significant; and The effect customer satisfaction on word of mouth are positive significant.